Systematic review of outcome measures following chemoradiotherapy for the treatment of anal cancer (CORMAC). (17th April 2018) - Fish, R.; Sanders, C.; Ryan, N.; der Veer, S. Van; Renehan, A. G.; Williamson, P. R.
Abstract: Aim: Six Phase III randomized trials have determined the effectiveness of chemoradiotherapy as primary treatment for anal squamous cell carcinoma (ASCC), but outcomes reported in these trials varied widely, hindering evidence synthesis. To improve reporting in all future trials, we aim to develop a core outcomes set (COS). As the first stage of COS development, we undertook a systematic review to summarize the outcomes reported in studies evaluating chemoradiotherapy for ASCC. Method: Systematic literature searches identified studies evaluating radiotherapy or chemoradiotherapy for ASCC. Outcomes and accompanying definitions were extracted verbatim and categorized into domains. Results: From 5170 abstracts, we identified 95 eligible studies, reporting 1192 outcomes and 533 unique terms. We collapsed these terms into 86 standardized outcomes and five domains: survival; disease activity; life impact [including quality of life (QoL)]; delivery of care; and toxicity. The most commonly reported domains were survival and disease activity, reported in 74 (86%) and 54 (62%) studies, respectively. No outcome was reported in every publication. Over half (43/86) of the standardized outcome terms were reported in fewer than five studies, and 21 (25%) were reported in a single study only. There was wide variation in definitions of disease‐free survival, colostomy‐free survival and progression‐free survival (PFS). Anal continence was reported in only 35 (41%) studies. Conclusion: Outcomes reported in studies evaluating chemoradiotherapy for ASCC were heterogenous and definitions varied widely. Outcomes likely to be important to patients, such as ano‐rectal function, toxicity and QoL, have been neglected. A COS for future trials will address these issues.